You'll Like It Better If It's...SARAN in Auto Seat Covers... - Dow Chemical Company (1952)
Color print advertisement for Saran fabric, made from Saran textile monofilaments. Saran is the trade name for polyvinylidene chloride, which can be formed into monofilaments or a thin plastic film. The advertisement features illustrated scenes showing the different uses of Saran, including two men standing with a window screen, upholstered car seats, and a set of outdoor furniture. The accompanying text describes different uses of Saran fibers in upholstery, fabrics and other consumer goods.
Keywords: Advertising; Dow Chemical Company; Chemical industry; Corporations; Plastics; Plastics industry and trade; Automobiles--Upholstery; Textile fabrics; Textile industry